Influence of toxoplasmosis on acetylcholinesterase activity, nitric oxide levels and cellular lesion on the brain of mice - Tonin A.A. (2014)
The objective of this study was to investigate the activity of acetylcholinesterase (AChE), nitrite/nitrate (NOx) levels, as well as the biomarkers of cellular damage in the brain of mice experimentally infected with Toxoplasma gondii. Sixty mice were divided into two experiments: in experiment I the mice were infected with T. gondii/RH strain, while in experiment II they were infected with T. gondii, strains VEG and ME-49. Our evaluations were carried out on brain homogenized samples, assessing the AChE and glutathione reductase (GR) activities, and NOx, TBARS and AOPP levels in all the infected animals, compared with the control group. In both experiments, I and II, it was observed an increase in the activity of AChE and GR, as well as in the levels of NOx in the brain of infected mice with T. gondii. TBARS levels were increased in mice infected with the three different strains, RH, ME-49, and VEG. AOPP concentration was increased only in mice infected with the RH strain. Animals infected with the strains VEG and ME-49 showed histological lesions, associated with the presence of the parasite in the brain. Therefore, the infection by T. gondii is able to interfere in cholinesterase activity and NO levels, in association with oxidative stress and histological lesion. © 2014 Elsevier GmbH.